Fischer-Tropsch synthesis using iron supported on potassic LTL zeolite and modified with Cs - Gallegos, Norma Graciela (2005)
Iron catalysts, to be used in the Fischer–Tropsch reaction were prepared using zeolite LTL and zeolite LTL modified with cesium, as supports. X-ray diffraction, specific surface area, atomic emission and absorption spectroscopies, Mo¨ssbauer spectroscopy in controlled atmosphere, between room temperature and 22 K, H2 chemisorption and volumetric oxidation were used to characterize the solids. Comparing both catalysts, the Cs presence generates a solid with a lower reducibility degree and a lower quantity of Fe0 microcrystals inside the pore structure, leading to a lower activity per gram and a higher olefins/paraffins ratio.